Tuberculosis interventions to prevent transmission of infection in health care workers: a systematic review - Schmidt, Bey-Marrie (Department of Public Health and Family Medicine, 2016)
Background: Tuberculosis is a major cause of morbidity and mortality as an estimated 8.6 million people developed TB and 1.3 million died from the disease in 2012. The number of deaths is high given that TB can be prevented. Health care workers are an at - risk group, since they are frequently in contact with infectious patients and/or work with infectious products. The World Health Organisation has declared the importance of finding innovative tools and strategies to prevent TB and implementing them successfully, especially for those with a high risk of TB transmission. Methods: This systematic review aims to undertake a quantitative review of tuberculosis interventions for health care workers in health care settings, so as to assess whether these interventions are effective in reducing the transmission of tuberculosis infection and disease. We will preferably include experimental studies, such as, randomised - controlled trials, but observational studies, such as controlled before and after studies and cohort studies will also be included in the absence of randomised - controlled studies. We will search databases, such as Medline, Scopus, Trip, LILACS and various trial registries. A hand search of reference lists of identified articles, abstracts, conference proceedings and campaign materials will be performed. Grey literature sites will also be used for the search. Data will be extracted using a single form. The quality of each study will be assessed in terms of selection bias, performance bias, attrition bias and detection bias. Thereafter a meta - analysis will be produced and subgroups will be analysed according to the three intervention types. Clinical and statistical significance will be determined for the included studies, and descriptive narratives of heterogeneous studies will be written. Discussion: Our results will be useful to policy - makers and public health officials for the prioritisation of those interventions identified as effective and critical .